Multi-Omics Analyses Reveal the Molecular Mechanisms Underlying the Adaptation of Wheat (Triticum aestivum L.) to Potassium Deprivation - Zhao, Yong; Sun, Ruoxi; Liu, Haodong; Liu, Xiaowei; Xu, Ke; Xiao, Kai; Zhang, Shuhua; Yang, Xueju; Xue, Cheng (Frontiers in Plant Science, 2020)
Potassium (K) is essential for regulating plant growth and mediating abiotic stress responses. Elucidating the biological mechanism underlying plant responses to K-deficiency is crucial for breeding new cultivars with improved K uptake and K use efficiency. In this study, we evaluated the level of genetic variation among 543 wheat associations differing in K-deficiency tolerance at the seedling and adult plant stages. Two accessions, KN9204 and BN207, were identified as extremely tolerant and sensitive to K-deficiency, respectively. The accessions were exposed to normal and K-deficient conditions, after which their roots underwent ionomic, transcriptomic, and metabolomic analyses. Under K-deficient conditions, KN9204 exhibited stronger root growth and maintained higher K concentrations than BN207. Moreover, 19,440 transcripts and 162 metabolites were differentially abundant in the roots of both accessions according to transcriptomic and metabolomic analyses. An integrated analysis of gene expression and metabolite profiles revealed that substantially more genes, including those related to ion homeostasis, cellular reactive oxygen species homeostasis, and glutamate metabolic pathway, were up-regulated in KN9204 than in BN207 in response to low-K stress. Accordingly, these genes may have unique regulatory roles affecting plant K-starvation tolerance. These findings may be useful for further clarifying the molecular changes underlying wheat root adaptations to K deprivation.